Trastorno de depresión mayor con ansiedad leve en joven de 20 años de la Universidad Técnica de Ambato - Ramirez Poma, Gregory Daniel (2021)
The present research aims to analyze and present the process of care and treatment for major depression disorder with the presence of mild anxiety, in a twenty-year-old girl from the Technical University of Ambato. To carry it out, the application of different resources such as clinical history (CH), clinical observation and semi-structured interview, as well as application of the Beck Depression Inventory have been used. It is important to point out that the depressive state is not explained by a specific origin but rather by the variety of factors that cause it, in addition to this, by not being treated in a timely manner, it can cause a second underlying problem, as in this case has been a picture of mild anxiety Thus generating comorbidity between Major Depression Disorder and mild anxiety, a serious problem that led the patient to a permanent dysfunctional state.